UPAYA MENINGKATKAN HASIL BELAJAR FORHAND DAN BACKHAND BULUTANGKIS MELALUI MODIFIKASI RAKET KAYU PADA SISWA - Sudirman, Ridwan; Aryadi, Dedi (STKIP Setiabudhi, 2021)
The purpose of this research is to create a modification product of racket modification media from wood to improve forhand and back hand training in badminton games. The research approach used is development research. The results of the study obtained aspect 1 value of